Top 100 Most-Cited Articles on Enhanced Recovery After Surgery: A Bibliometric Analysis and Visualized Study - He, Liping; Lu, Lulu; Su, Shengjie; Lin, Qiang; Sheng, Chan (Frontiers in Surgery, 2022)
Background: Enhanced recovery after surgery (ERAS) protocol is widely implemented in surgeries, this study aimed to reveal the characteristics of the 100 most cited original articles in the field of ERAS research. Methods: Literature were retrieved in the Web of Science (WOS) database, the 100 most cited original articles were identified and their characteristics were analyzed, including trends of publications and citations; contributions from countries, institutions, and authors; co-cited authors and journals in the references; served surgeries, research endpoints, keywords; and level of evidence. Results: There was a rising trend in the yearly publications and citations. Denmark and the USA contributed the largest number of highly cited papers. The University of Copenhagen was the most influential institution. Kehlet, Henrik was the most influential author. British Journal of Surgery was the most often published and cited journal. ERAS protocols were overwhelmingly implemented in colorectal surgeries. The most focused endpoints were “length of stay”, “complications”, and “readmission”. The most frequently used keywords were “fast track”, “length of stay”, and “laparoscopy”. The keyword “enhanced recovery after surgery” burst since 2012. More than half of the highly cited articles presented level Ⅳ evidence, there was no correlation between citations (densities) and levels of evidence. Conclusions: The highly cited research overwhelming implemented ERAS in colorectal surgeries, the “length of stay” was the most focused element, Kehlet, Henrik was the most influential researcher. Most of the highly cited ERAS had low levels of evidence, the total number of citations was not relevant to the level of evidence. Studies with high levels of evidence are still required in the future.